Breaking the silence: A feminist call to action. (12th April 2016) - Parizeau, Kate; Shillington, Laura; Hawkins, Roberta; Sultana, Farhana; Mountz, Alison; Mullings, Beverley; Peake, Linda
Abstract : Mental health and wellness are issues of growing concern on campuses across North America. While feminist geographers have done important work over the years to organize, mentor, gather, and publish collectively on issues related to wellness, much more remains to be done. In this article, we—a collection of scholars who identify as feminist geographers—comment on our experiences of mental wellness in the academy, and engage in a collective self‐analysis to better understand the silences, invisibilities, and hesitancies surrounding these issues on the campuses where we work. We argue that not only does more attention need to be brought to bear on this topic, but also that it needs to be more broadly understood. We find that there are institutional, cultural, political, and intersectional factors that impede active engagement with mental health and wellness in the academy, and we discuss strategies for deeper engagement with such important issues for our students, colleagues, research participants, and ourselves. Briser le silence : un appel à l'action féministe: La santé mentale et le bien‐être mental sont des questions qui suscitent des préoccupations croissantes au sein des campus universitaires nord‐américains. Alors que, dans l'ensemble, les géographes féministes ont réalisé des travaux importants au cours des années afin de s'organiser, de conseiller, de se réunir et de publier sur des questions relatives au bien‐être, le chemin à parcourir est encore long. Cet article nous amène, en tant que regroupement de chercheures qui se présentent comme des géographes féministes, à formuler des observations sur nos expériences de bien‐être mental dans le monde universitaire, et à mener une autoanalyse collective afin de mieux comprendre les silences, occultations et réticences entourant ces questions sur nos campus. Nous avançons qu'au‐delà du fait que ce sujet requiert une attention accrue, qu'il doit également s'ouvrir sur une perspective élargie. Nos résultats ont identifié des facteurs institutionnels, culturels, politiques et entrecroisés qui freinent la mobilisation autour de la santé mentale et du bien‐être mental dans le monde universitaire. Enfin, nous discutons à propos de stratégies propices à une mobilisation accrue sur ces questions importantes pour nos étudiants, collègues, sujets de recherche, et nous‐mêmes. Key Messages: Mental health and wellness are issues of growing concern on North American campuses. A feminist geography perspective reveals that there are cultural, institutional, political, and intersectional factors that impede active engagement with mental health and wellness in the academy. We encourage geographers to consider mental health and wellness as professional development issues of concern to us all.